A case of meningitis caused by streptococcus pyogenes in a child with ventriculoperitoneal shunt and ommaya reservoir - (:unkn) unknown (My University, 2013)
Streptococcus pyogenes az rastlanan enfeksiyonların iyi bilinen bir nedenidir. Akut bakteriyel menenjit nede- ni olarak bu patojen nadirdir. Biz bu makalede ventri- küloperitoneal (VP) şantı ve bilateral Ommaya rezervu- arı olan ve son ameliyatından sonra grup A streptokok (GAS) menenjiti gelişen bir çocuğu sunduk. Hasta VP şant ve Ommaya rezervuarlarının çıkarılması ve 21 gün süreyle vankomisin, seftriakson ve klindamisin verile- rek tedavi edildi. GAS menenjiti için birçok predispo- zan faktör rapor edilmiş olsa da bu Ommaya rezervu- arı ve VP şant ilişkili ilk rapor edilen makaledir. Klinisyenler sporadik vakaların olabileceği konusunda uyanık olmalıdır ve hızla tedavi uygulanması durumun- da daha olumlu sonuçlar elde edilecektir. (J Pediatr Inf 2013; 7: 35-8)

Streptococcus pyogenes is a well-known cause of invasive infections. However, acute bacterial meningi- tis caused by this pathogen is unusual. Herein, we presented a child with ventriculoperitoneal (VP) shunt and bilateral ommaya reservoir who developed group A streptococcal (GAS) meningitis a month after the last neurosurgery operation. The patient was treated with removal of VP shunt and ommaya reservoir and antibi- otic therapy including vancomycin, ceftriaxone and clindamycin for 21 days. Although many predisposing factors have been described for GAS meningitis, this is the first report of an association between ommaya reservoir and VP shunt due to S. pyogenes meningitis. Clinicans should be aware that sporadic cases can occur and if it is treated promptly, the outcome tends to be favourable. (J Pediatr Inf 2013; 7: 35-8)
Ventriküloperitoneal şantı ve ommaya rezervuarı olan çocukta streptokokkus pyogenes menenjiti
Keywords: Enfeksiyon Hastalıkları